Mercado de capitales, intermediación financiera y crecimiento económico en el Perú (1995-2008) - Cortez cortez, Gaby (2009)
It examines the relationships between the financial system, the capital markets and the growth of the Peruvian economy, using statistical information for a period between 1995-2008. The changes brought about by the financial sector liberalization, deregulation and liberalization of the economy of more than a decade ago are sufficient grounds to conduct studies to evaluate possible causes of long-term relationships between these variables.To establish these potential relationships we have been applied econometric techniques, using a vector autoregressive model (VAR) to confirm orden y the existence of causal statistical, using the Augmented Dickey Fuller test for determining the existence of unit roots in the series, and Johansen test for explaining the existence of cointegration for the whole series.